Tolerance in The Form of Ancak Agung - Rizal, Syaiful; Qiptiyah, Titin Mariatul; Arifin, Zainal (Proceedings of Annual Conference for Muslim Scholars, 2025)
Religious celebrations often serve as a space for reflection on social values. This study attempts to analyze the role of the Ancak Agung tradition in Jember, a communal ritual during the celebration of the Prophet's birthday, as a mechanism for strengthening tolerance and social cohesion amidst a heterogeneous society. This study views Ancak Akbar not only as a religious tradition and ritual, but also as a mediating arena for social interactions that transcend group boundaries. This research uses a qualitative case study approach, using triangulation techniques for data validation. Data analysis focuses on the patterns of interaction that occur and the community's interpretation of the symbolic meaning of Ancak Agung in the context of community. This research found that Ancak Agung functions as a "liminal space" that strips away primary identities. Ritually, this tradition creates a uniform spiritual purpose, manifested in the inclusive distribution of Gunungan Ancak, regardless of affiliation. Interactions are dominated by a spirit of mutual cooperation during preparation and sharing during distribution, effectively breaking down social barriers. Furthermore, the Ancak Agung Tradition has a significant social impact, strengthening solidarity and reducing prejudice between groups. This sharing ritual demonstrates that tolerance is a culturally institutionalized social practice. Ancak Agung serves as a model of local wisdom that is effective in managing diversity and maintaining social harmony in Jember.